2017
DOI: 10.20944/preprints201709.0128.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research-Based Training: Methodological Characteristics and Results of the Analysis of Educational Programs

Abstract: Abstract:The purpose of the article is to determine the peculiarities of using of teaching elements 11 of research-based training at the Institute of Human Sciences of Borys Grinchenko Kyiv University. 12Based on the focus group methodology, the authors identify the key methodological characteristics 13 of research-based training, which have been put into basis of analysis of educational programs for 14 the purpose of determining the application of tasks that contribute to the development of research 15 skills… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…On the basis of the research results, scholars are defined the research-based training as a type of learning that has its purpose, content, methods, form of organization and means, and can be implemented through a specific set of learning technologies. Confirmation of such an opinion is found in the works of well-known foreign scientists, whose research was related to the methodological basis of research-based training (Pavliuk et al, 2017).…”
Section: Research-based Training For Preparation Of Professionals Of mentioning
confidence: 74%
See 1 more Smart Citation
“…On the basis of the research results, scholars are defined the research-based training as a type of learning that has its purpose, content, methods, form of organization and means, and can be implemented through a specific set of learning technologies. Confirmation of such an opinion is found in the works of well-known foreign scientists, whose research was related to the methodological basis of research-based training (Pavliuk et al, 2017).…”
Section: Research-based Training For Preparation Of Professionals Of mentioning
confidence: 74%
“…Research-based training is a complex of pedagogical goals, which are united with the main tasks in the development of research competence of students (development of skills for setting the research task and finding ways to solve it) (Pavliuk et al, 2017).…”
Section: Research-based Training For Preparation Of Professionals Of mentioning
confidence: 99%
“…Good research-based learning practices should involve 4 aspects: 1) research results should have an impact on the curriculum, 2) teaching and learning methods should be research-based, 3) learning must use the elements of research,4) RBL should be able to develop a context inclusive research (Srikoon, 2014). Consequently, according to a study in Ukraine, it can be concluded that research-based learning has complex pedagogical goals, coupled with the fundamental task of developing student research competencies (developing skills to design a research task and finding ways to overcome it) (Pavliuk, Liakh, Bezpalko, &Klishevych, 2017).…”
Section: Introductionmentioning
confidence: 99%